THE EFFECT OF SERVICE QUALITY ON CONSUMER BUYING INTEREST AT THE ALTIC HOUSEWARE STORE IN MEDAN - Alda Febriani; Teuku Fahmi; Teguh dwi putra (Universitas Dharmawangsa Medan, 2026)
This study aims to determine the effect of service quality on consumer purchasing interest at the Altic Houseware Store in Medan. The background of this study is based on the increasingly tight competition in the household goods retail business which requires business actors to improve service quality to attract and retain consumers. Service quality is considered as one of the important factors that can influence consumer purchasing interest. The research method used is a quantitative approach with an associative research type. The population in this study were all consumers of the Altic Houseware Store in Medan with an average of 4,500 people per month. The research sample was determined using the Slovin formula of 98 respondents with an accidental sampling technique. Data collection techniques were carried out through a questionnaire with a Likert scale. Data analysis used validity tests, reliability tests, classical assumption tests, simple linear regression analysis, t-tests, and coefficients of determination (R²). The results showed that service quality had a positive and significant effect on consumer purchasing interest. This is evidenced by the calculated t-value of 16.337 with a significance level of 0.000 (<0.05). The regression equation obtained is Y = 5.873 + 0.418X, indicating that any increase in service quality will increase consumer purchasing interest. The coefficient of determination (R²) of 0.735 indicates that service quality can explain 73.5% of the variation in consumer purchasing interest, while the remaining 26.5% is influenced by other factors outside the study. Thus, it can be concluded that service quality plays a very important role in increasing consumer purchasing interest at the Altic Houseware Store in Medan. Therefore, the store is advised to continuously improve service quality to increase consumer appeal and loyalty.